EFFECT OF STARVATION AND REFEEDING ON RED MUSCLE ORGANIC CONSTITUENTS OF TILAPIA MOSSAMBICA (PETERS) - Rao, M V Chalapathy; Bharathi, D; Bhaskar, M; Govindappa, S (Indian Journal of Fisheries, 2011)
Short-term starvation and refeeding caused slight depletion in total proteins,total carbohydrates and total lipids. But the long-term starvation and refeedingrecorded increase in the carbohydrate content, with marked depletion in the totalprotein and lipid contents, particularly the cholestrol, indicating overshot accllmlliiltiollof caIbohydrates in the tissue. The process of starvation and refeedingseems to decrease effectively the Ghole.1)~rol content in the muscle.